2016
DOI: 10.1177/1065912916658128
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation Wars, Legislative Time, and Collateral Damage

Abstract: Presidents often see a Supreme Court nomination as an opportunity to leave a lasting mark on policy. Recent studies speculate that focusing on Supreme Court nominees affects presidential success beyond the confirmation process, but this has not been established systematically. We develop and test a hypothesis stating that presidents who get into a battle to promote a controversial Supreme Court nominee will see delays and failures in their efforts to promote their legislative agenda in the Senate and fill lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Contrary to Expectation 6 but in line with our findings from the descriptive analysis above, we find no evidence that President Trump, the only president so far to enjoy the effects of the rules change for transition vacancies, has been able to use the rules changes to his advantage when making nominations to the federal bench. However, it must be noted that President Trump was the only president within these data to also inherit a Supreme Court vacancy, which we know captures time, attention, and political capital from presidents with respect to other priorities (Madonna, Monogan, and Vining 2016).…”
Section: Figure 1 Time To District Court Nominations By Blue Slip Comentioning
confidence: 95%
See 2 more Smart Citations
“…Contrary to Expectation 6 but in line with our findings from the descriptive analysis above, we find no evidence that President Trump, the only president so far to enjoy the effects of the rules change for transition vacancies, has been able to use the rules changes to his advantage when making nominations to the federal bench. However, it must be noted that President Trump was the only president within these data to also inherit a Supreme Court vacancy, which we know captures time, attention, and political capital from presidents with respect to other priorities (Madonna, Monogan, and Vining 2016).…”
Section: Figure 1 Time To District Court Nominations By Blue Slip Comentioning
confidence: 95%
“…A more opaque calculation occurs when presidents are faced with the decision of which vacancies to prioritize. Presidential time and influence are not infinite, and prior research has shown that presidents face an opportunity cost for making efforts on behalf of judicial nominees (Madonna, Monogan, and Vining 2016). While much of the searching for, vetting, and shepherding of judicial nominees has been delegated to entities such as the White House Counsel's office or the Office of Legal Policy within the Department of Justice, 2 there are limitations to how many nominations such institutions can make or manage at any given time.…”
Section: Politics and Judicial Nominationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars consider his failed confirmation to be an important variable in models of advice and consent. 2 Judicial confirmations are more contentious, and interest groups are more influential in the advice and consent process now than they were before Bork's failed confirmation (Cameron, Kastellec, and Park 2013;Epstein and Segal 2005;Madonna et al 2016;Scherer, Bartels, and Steigerwalt 2008; but see Cohen 1998). The result of this contention is senatorial delay and even failure to vote to confirm nominees to the Supreme Court, and other federal courts as well (Bell 2002;Binder andMaltzman 2002, 2004;Bond, Fleisher, and Krutz 2009;Epstein and Segal 2005;Shipan and Shannon 2003).…”
mentioning
confidence: 99%